Using TermoDeck System for Pre-Cooling/ Heating to Control the Building Inside Conditions - Mohammad, Wahid S.; Murtadha, Talib K.; Ahmed, Karrar A. (Al-Khwarizmi Engineering Journal, 2014)
In this paper, experimental study has been done for temperature distribution in space conditioned with Ventilation Hollow Core Slab (TermoDeck) system. The experiments were carried out on a model room with dimensions of (1m 1.2m 1m) that was built according to a suitable scale factor of (1/4). The temperature distributions was measured by 59 thermocouples fixed in several locations in the test room. Two cases were considered in this work,  the first one during unoccupied period at night time (without external load) and the other at day period with external load of 800W/m2 according to solar heat gain calculations during summer season in Iraq. All results confirm the use of TermoDeck system for ventilation and cooling/heating purposes in arid and hot climate for its ease, simple and good comfort performance and to save energy and improve the overall energy performance of the building by reducing the peak load.